Responsivitas Pelayanan Publik oleh Kepolisian Resort Mojokerto dalam Menangani Pengaduan Masyarakat - Ihram Kustarto; Amirul Mustofah; Ika Devy Pramudiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Responsive public service plays a crucial role in building public trust in police institutions, particularly in handling citizen complaints. This study aims to examine the responsiveness level of Mojokerto Police Resort in managing public complaints and the factors influencing it. The research adopts a qualitative descriptive approach, utilizing data collection methods such as in-depth interviews, direct observations, and document studies. Participants include officers from the Integrated Police Service Center (SPKT), Women and Children Service Unit (PPA), community members who have filed complaints, as well as community leaders and NGOs involved in overseeing public services. Data analysis was conducted using Miles and Huberman’s model, which includes data reduction, presentation, and conclusion drawing. The findings reveal a varied level of awareness among the community regarding complaint channels, as well as differences in ease of access. Physical channels such as suggestion boxes and direct reporting at police stations are more familiar and accessible but face challenges related to communication effectiveness and evidence collection. Meanwhile, online platforms like social media and the official website are less recognized by the public, compounded by limited digital literacy and internet access in certain areas. Furthermore, the complaint handling process needs to be straightforward, transparent, and professional to ensure that the community feels respected and confident in the service. Factors affecting responsiveness include response speed, ease of access across multiple channels, and the professionalism of officers handling cases. Perceptions of transparency and openness in procedures also significantly influence community trust. Strategically, Mojokerto Police Resort has made efforts to develop digital complaint systems and enhance staff capabilities. However, further improvements are necessary in community education and awareness programs to increase familiarity and confidence in digital channels. The significance of high responsiveness is reflected in its strategic benefits, such as early identification of security disturbances, strengthening police legitimacy, and improving overall public service quality. Effective responsiveness fosters better relationships between officers and the community, enhances trust, and contributes to a safer and more orderly environment. Therefore, adopting modern, innovative, and technology-based complaint systems should be prioritized to reform police services. Overall, the responsiveness of Mojokerto Police Resort’s complaint handling system serves as a key indicator for the success of quality and equitable public services. By improving officer professionalism, infrastructure, and community outreach, it is expected that Mojokerto Police can enhance responsiveness, reinforce community trust, and deliver excellent, transparent, and accountable services. Such efforts not only improve the police institution’s reputation but also strengthen democratic foundations and social justice in the Mojokerto region.